The Influence Of Palm Stearin Content On The Rheological Behaviour Of 316L Stainless Steel Mim Compact - Omar, Mohd Afian; Subuki, Istikamah; Abdullah, Norsyakira; Ismail, Mohd Fahies (Journal of Science and Technology, 2010)
Metal Injection Molding (MIM) is a growth technology for producing metal component. Feedstock preparation for MIM is a very crucial step since deficiencies in quality of the feedstock cannot be corrected by subsequent processing adjustments. Hence, it is important that the feedstock is homogeneous and free from powder-binder separation or particle segregation. One of the great concerns in the quality of the feedstock is the formulation of binder. The present mixing study was conducted with 316L stainless steel with a locally binder system; palm stearin and polyethylene. This study investigates the influence of the PS content in the binder formulation via rheological characteristics and various mixing conditions. The results show that good homogeneity of the feedstock prepared for injection moulding of 316L SS powder with the palm stearin as a based binder system.